PENGARUH POLITIK PINTU TERBUKA TERHADAP MASYARAKAT PEDESAAN DI JAWA - Utami, Santi Muji (Paramita: Historical Studies Journal, 2011)
The second half of the nineteenth century Dutch colonial government has issued the Law relating to economical politics in the Netherlands Indies, whose development was accompanied by a variety of social phenomena, especially among native communities.ÃÂ The influence of the open door politics has given impact on the rural population, because they are directly confronted with colonial interests in the arena of international commerce.ÃÂ Exploitation on various aspects of the lives of the rural population cannot be avoided.ÃÂ Therefore, entering the twentieth century.ÃÂ deterioration of living conditions that lead to poverty cannot be avoided. Socio-economic structure in rural indigenous communities are basically unbalanced and uneven.ÃÂ During Dutch colonial rule, foreign private interest was strong enough related to the international market.ÃÂ International markets have tended to act as an